Removal of lead ions from wastewater using multi walled carbon nanotubes modified with sodium lauryl sulfate - Suliman, Malaz (2017)
Multi walled carbon nanotubes (MWCNTs) modified with sodium lauryl sulfate (SLS) were synthe-sized, characterized and successfully used for the removal of Pb2+ from aqueous solutions. Adsorp-tion results revealed that this surface modification increased adsorption capacity from 3.84 to 141 mg/g. Adsorption on raw-MWCNTs followed the Langmuir isotherm with qm = 3.84 mg/g and KL = 0.29 L/mg, whereas adsorption on SLS-MWCNTs followed the Freundlich isotherm with n = 2.50 and KF = 15.40 mg 0.6·L0.4/g. Adsorption kinetics on raw and modified MWCNTs followed a pseudo second order law with rate constants 0.11 and 0.06 g/mg·min, respectively. Thermodynamic studies showed that Pb2+ was physisorbed on both adsorbents, with apparent Gibbs free energy, ∆G °,values of –0.45 and –9.21 kJ/mol at 25°C, respectively. Magnetite derivatives of SLS-MWCNTs were synthesized and used for Pb2+ removal. Batch adsorption studies on the magnetite and non-magnetite SLS-MWCNTs gave similar results. The enhanced density of the magnetite pellets of SLS-MWCNTs allowed for their use in a packed bed column. Column operation modeling results showed that the modified dose response model most adequately describes the column data with parameter values qmdr = 28.4 mg/g and a’ = 3.47 mg–1.